The Effect of Corporate Social Responsibility Disclosure and Financial Leverage on Processed Food Industry Companies’ Profitability That Listed at BEI - Yusran, St. Chairun Annisa; Akib, Haedar; Baharuddin, Aris; Aslinda, Andi (Universitas Negeri Makassar, 2022)
This study aim to determine how Corporate Social Responsibility Disclosure and Financial Leverage which is proxied by Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) influence company’s Profitability which is proxied by Return on Equity (ROE) either Partially or Simultaneously where Processed Food Companies that registered at IDX 2017-2020 year period become the object of this research. The type of this research is quantitative research. The technique of data collection uses secondary data documentation in the form of annual report. The sample used is the sample that selected using purposive sampling technique which is 4 companies so the annual report that becomes the object is as many as 16 annual reports. The data obtained from the research results were processed using the SPSS version 25 software program which consisted of the Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, Correlation Coefficients, and Determination Coefficients.The result of the research showed that the indicators used for each variable indicated that CSR disclosure variable has a significant effect on ROE, DAR and DER doesn’t have significant effect on ROE of processed food companies listed on the Indonesia Stock Exchange period 2017-2020 year period. This is evidenced by the Correlation Test, T Test and F Test, as well as the Coefficient of Determination Test on the data that has been obtained.